Evaluate the Psychometric Properties of Chinese Version Social Media Use and Positive Body Image Scale Among High School Students in China. - Yueyi Liu; Hooi Lian Lim (Pertanika Journal of Social Sciences & Humanities, 2025)
The purpose of this study was to assess the psychometric properties of the Chinese versions of the Positive Body Image Scale for Adolescents (PBIAS) and the Social Media Use Integration Scale (SMUIS) using Item Response Theory, specifically the Rasch model to address the lack of validated instruments to assess positive body image and social media use among Chinese adolescents. This study revealed that C-PBIAS and C-SMUIS generally had good reliability and validity. Correlation analysis results revealed a significant relationship between positive body image and social media use among Chinese high school students, which is a negative correlation. This means that social media use has a negative effect on positive body image among high school students in China. This study contributes to the development of culturally relevant psychometric instruments and provides insights into the impact of social media on the physical and mental health of Chinese adolescents.